2004
DOI: 10.1007/s00421-004-1071-z
|View full text |Cite
|
Sign up to set email alerts
|

Scaling or normalising maximum oxygen uptake to predict 1-mile run time in boys

Abstract: There is still considerable debate and some confusion as to the most appropriate method of scaling or normalizing maximum oxygen uptake ( _ V O 2max ) for differences in body mass (m) in both adults and children. Previous studies on adult populations have demonstrated that although the traditional ratio standard _ V O 2max (ml kg )1 min )1 ) fails to render _ V O 2max independent of body mass, the ratio standard is still the best predictor of running performance. However, no such evidence exists in children. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
4
17
0
3
Order By: Relevance
“…A similar result was obtained when investigating the energy cost of running for 12-year-old boys (Nevill et al 2004). The authors confirmed the best predictor of boys' 1-mile run speed was the traditional ratio standard, maximum oxygen uptake (ml kg À1 min À1 ).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…A similar result was obtained when investigating the energy cost of running for 12-year-old boys (Nevill et al 2004). The authors confirmed the best predictor of boys' 1-mile run speed was the traditional ratio standard, maximum oxygen uptake (ml kg À1 min À1 ).…”
Section: Introductionsupporting
confidence: 79%
“…There is a considerable body of knowledge investigating the energy cost of running in both adults (Margaria et al 1963;Dill 1965;Nevill et al 1992) and children (Nevill et al 2004). Indeed, when investigating a group of recreationally active adults, men (N=112) and women (N=92), Nevill et al (1992) were able to confirm that using both _ V O 2 max 1 min À 1 and body mass (m) as predictor variables, the best predictor of 5-km running performance (m s À1 ) was, Run speed ðm s À1 Þ ¼ 84:3ð _ V O 2 max Þ 1:01 ðmÞ À1:03 :…”
Section: Introductionmentioning
confidence: 99%
“…This logically and statistically performs better than linear models. These assertions in regard to the current study are also consistent with prior studies on the same topic in adults (9,14,15) and children (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…The performance capabilities of children are typically less than those of adults, and understanding to what extent performance differences are attributable to differences in body size is important in domains such as school physical education, sport performance, and talent identification. Moreover, allometric modeling has been demonstrated as superior in the prediction of children's physical performance (16,17). Although the outcomes of this study show some similarity between the linear and allometric models presented here, the allometric model performs marginally better than the linear model; this is because it predicts a greater amount of the variance in actual peak power and has a smaller coefficient of variation than the linear model.…”
Section: Discussionmentioning
confidence: 59%
“…Scaling methods utilized include ratio scaling (per body mass ratios thus size dependent); linear regression scaling and algometric scaling (allows for size adjusted ratios and the examination of different growth rates as part of the growth process). Longitudinal scaling methods include ontogenetic allometry which allows for the examination of different growth rates as part of the individual growth process and multilevel modeling (Armstrong & Van Mechelen, 2008;Armstrong, Welsman, & Kirby, 1998;Bar-Or & Rowland, 2004;Nevill, 1997;Nevill & Holder, 1994;Nevill, Rowland, Goff, Martel, & Ferrone, 2004).…”
Section: Fitnessmentioning
confidence: 99%